2001
DOI: 10.1007/s004280000303
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of human beta-defensin 2 in keratinized and non-keratinized oral epithelial lesions; immunohistochemistry and in situ hybridization

Abstract: Human beta-defensin(hBD)-2, an antimicrobial peptide, is produced by various epithelial cells. Because hBD-2 expression in the oral epithelium has not been assessed, we investigated its localization in normal oral epithelium and epithelial lesions. hBD-2 expression was studied using immunohistochemistry and in situ hybridization on formalin-fixed, paraffin-embedded tissue sections from 30 cases of squamous cell carcinoma and 6 cases of leukoplakia. Immunostaining for hBD-2 was more intense in hyperkeratinized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 11 publications
(21 reference statements)
7
29
0
1
Order By: Relevance
“…Also, most HBD-2 heavily stained cells showed enlarged cell size characteristic of more differentiated keratinocytes. This observation correlates correlates to the reports by Liu et al [10] in dermal tissue and by Abiko et al [33] in oral mucosal tissue that HBD-2 mainly expressed in upper layers of more differentiated epithelial cells.…”
Section: Immunohistochemical Analysis Of Hbd-2 Expression In Sin18-hbsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, most HBD-2 heavily stained cells showed enlarged cell size characteristic of more differentiated keratinocytes. This observation correlates correlates to the reports by Liu et al [10] in dermal tissue and by Abiko et al [33] in oral mucosal tissue that HBD-2 mainly expressed in upper layers of more differentiated epithelial cells.…”
Section: Immunohistochemical Analysis Of Hbd-2 Expression In Sin18-hbsupporting
confidence: 92%
“…Bacteria and cytokines IL-1 and TNFα upregulate HBD-2 expression in lung and skin epithelial cells [10,28] and induction of HBDs by these stimuli is differentially regulated involving multiple mechanisms [29]. Expression of HBDs in oral tissues has also been extensively studied [23,[30][31][32][33][34][35][36][37][38][39][40]. In gingival epithelium, variable expression levels of HBD-1, -2 or -3 are found in either healthy or diseased gingival tissues [41,42] Previously, we transduced a number of non-HBD-2-expressing cell lines to produce HBD-2 with the notion that these cells may become part of the innate defense mechanisms against infection [6,49].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Tissue sections were stained by immunohistochemical analyses for the presence of human ␣-defensins 1 to 3 using a 1:1,000 dilution of mouse MAb anti-human defensin, clone DEF-3 (Serotec, Raleigh, NC). Human ␤-defensin-2 was detected using a 1:4,000 dilution of polyclonal rabbit anti-hBD-2 antiserum (Peptide Institute, Louisville, KY), as previously described (1). Human ␤-defensins 1 to 3 were detected following the described protocol below, using the respective affinity purified antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…In the observations of Abiko et al the increased expression of HBD-2 and decreased expression of HBD-1 were found in highly-differentiated, keratinized lesions, while in poorly differentiated, squamous call carcinomas the expression of HBD-2 was not detected at all [33]. Malignant neoplasms are very often accompanied by the inflammatory reaction, which, according to Abiko, may additionally stimulate the HBD-2 expression in some oral neoplasms.…”
Section: Defensins and Their Role In The Maintenance Of The Oral Cavimentioning
confidence: 91%
“…In many studies it was found that the β-defensin oral expression significantly rises in the presence of bacteria species responsible for the development of periodontitis, which include: Actinomycetes actinomycetemcomitans, Porphyromonas gingivalis and Fusobacterium nucleatum [6,25,28,33] and the induction of the HBD expression occurs in several ways, most probably with MAPK (mitogen-activated protein kinases) or NF-κB (nuclear factor κB) paths [1,4,14]. In this light the results of Bissell's et al research, who did not observe any elevation in the expression of the β-defensin 1-3 in the inflamed periodontal tissue, while the HBD-3 expression was significantly higher in the healthy controls than in their study group, may be considered surprising [29].…”
Section: The Expression and The Role Of Defensins In The Oral Cavitymentioning
confidence: 99%